Attracting young academics into the field of psychiatry and psychotherapy in Switzerland – The Zurich 'study focus on psychiatry' and training concept for medical psychotherapy. (August 2013) - Gerke, Wolfgang; Rufer, Michael; Schnyder, Ulrich
Abstract For several years the demand regarding psychiatrists in Switzerland can only be satisfied by recruiting colleagues from other countries. Given the global increase of mental disorders, initiatives encouraging young academics to choose psychiatry as their speciality, and enhancing the attractiveness of our field, are urgently needed. Two projects for the promotion of young academics are presented in this paper, one working with medical students, the other with residents in psychiatry. The Zurich 'Study Focus on Psychiatry' provides medical students with knowledge and key competencies in psychiatry at an early stage of their undergraduate training. This way, students are offered an opportunity to have a thorough look into psychiatry as a clinical specialism and as a science. The three-year psychotherapy training curriculum in medical psychotherapy provides residents in psychiatry and psychotherapy with specific training in either cognitive behavioural, or psychodynamic, or systemic psychotherapy. Additionally, and independent of the psychotherapeutic orientation they have chosen, all trainees attend joint sessions focusing on generic elements of psychotherapy and facilitating a hands-on transfer of psychotherapeutic principles into their clinical routine. These two projects aim at enhancing the attractiveness of psychiatry and psychotherapy as a speciality, and thus contributing to the promotion of young academics.